Isolation and identification of Pseudomonas sp. on dumbo catfish (Clarias gariepinus) in semi-intensive manner - Admi, Masda; Maulida, Rafdhayatul; Helmi, Teuku Zahrial; Winaruddin, Winaruddin; Akmal, Yusrizal (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
The aquaculture system in the maintenance of dumbo catfish is widely practiced by the community due to several advantages it offers. However, in terms of fish health, there is a risk of infection by Pseudomonas bacteria present in the environment. This study aims to isolate and identify Pseudomonas sp. bacteria in dumbo catfish (Clarias gariepinus) raised in a semi-intensive manner. A total of three samples of dumbo catfish were taken from ponds in Beurangong Village, Kuta Baro District, and nine samples from ponds in Dham Pulo Village, Ingin Jaya District, Aceh Besar Regency. The criteria for the samples were fish that clinically showed symptoms of disease caused by Pseudomonas sp. Each catfish had samples taken from the skin, liver, spleen, intestines, and gills for subsequent bacterial isolation and identification using the Carter method. Bacterial isolation was conducted using Nutrient Broth (NB) media. Identification utilized Plate Count Agar (PCA) media, Gram staining, and biochemical tests. The results showed bacterial growth in the NB media, and Pseudomonas bacteria were successfully isolated. The identification results on PCA media indicated Pseudomonas sp., and the biochemical tests identified it as Pseudomonas aeruginosa. This study concludes that in dumbo catfish raised semi-intensively, Pseudomonas sp. bacteria were isolated and identified in Beurangong Village, while in Dham Pulo Village, the identified species was Pseudomonas aeruginosa.